Complexo Carajás, Amazônia: the pretentious urbanizing footprints of a territory - Trevisan, Ricardo (2025)
In Brazil, the geopolitics adopted by the military government between 1964 and 1985 drove numerous actions and plans that promoted, among other fronts, the urbanization of the territory. In the state of Pará, the discovery in Serra dos Carajás (Carajás Mountains) of the largest iron ore reserve aroused the interest of foreign companies in the 1960s. As a support for the large-scale mineral exploration, a logistical contribution was necessary, promoting the implementation of infrastructure and the expansion or creation of urban centers. By consulting existing sources and documents, the history of this territory is revealed, pointing out and discussing the changes it has undergone in the last 50 years.